2019
DOI: 10.3349/ymj.2019.60.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Mechanism of Long Noncoding RNAs in Colon Cancer Development and Progression

Abstract: Colorectal cancer (CRC) is the second most common cause of cancer-related death worldwide, and its high rates of relapse and metastasis are associated with a poor prognosis. Despite extensive research, the underlying regulatory mechanisms of CRC remain unclear. Long noncoding RNAs (lncRNAs) are a major type of noncoding RNAs that have received increasing attention in the past few years, and studies have shown that they play a role in many biological processes in CRC. Here, we summarize recent studies on lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 83 publications
1
33
0
Order By: Relevance
“…Noncoding RNAs, especially the microRNAs, have been found to play key roles in CRC development in intestinal tissue [ 16 19 ]. In this study, we identified 20 miRNA biomarkers dysregulated in the colon adenomas, among which, the mir-224-5p and mir-203a were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNAs, especially the microRNAs, have been found to play key roles in CRC development in intestinal tissue [ 16 19 ]. In this study, we identified 20 miRNA biomarkers dysregulated in the colon adenomas, among which, the mir-224-5p and mir-203a were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been shown to play important regulatory roles in a variety of cellular processes including cell proliferation, differentiation, and development, and the aberrant expression of lncRNAs has been suggested to be involved in human diseases, such as cancer (Latos et al, 2012;Engreitz et al, 2013;Bouckenheimer et al, 2016;Renganathan and Felley-Bosco, 2017). In colorectal cancer, it has been reported that several lncRNAs can directly bind to proteins or act as miRNA sponges to participate in cellular signaling pathways such as b-catenin, p53, JAK/STAT, AKT/mTOR, and NF-kB, among others, thereby affecting cell cycle progression and/or EMT (epithelial mesenchymal transition) to control tumor cell growth, migration, and invasion (Kawasaki et al, 2016;Yang et al, 2017;Jiang et al, 2018;Sun et al, 2018;Tang et al, 2019). Many lncRNAs, such as CCAT1 and HOTAIR, are often associated with prognosis in clinical patients, and can be used as potential diagnostic markers for colorectal cancer (He et al, 2014;Svoboda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, they were identified as oncogenes or tumor suppressors, prognostic and diagnostic biomarkers and as therapeutic targets [ 11 13 ]. For instance, Tang and colleagues reviewed the implication of lncRNAs in colorectal cancer progression and figured out their potential clinical applications as novel diagnostic and prognostic biomarkers and therapeutic targets [ 14 ].…”
Section: Introductionmentioning
confidence: 99%